Producing Alkali Metal Hydrides from Hydroxides - Ibrahim, Ainee; Paskevicius, Mark; Humphries, Terry D.; Buckley, Craig E. (2024)
In this study, a novel method for producing different alkali metal hydrides (NaH, KH, RbH, and CsH) from their corresponding metal hydroxides (NaOH, KOH, RbOH, and CsOH) is presented. For the production of NaH from NaOH, a variety of metallic reducing agents (Mg, Al, Si, CaH2, Cr, Mn, and Sr) were investigated. The reactions took place in an autoclave reactor with paraffin oil at 250 °C and 14 bar of H2 pressure. Splitting the process into two steps (metal formation and hydrogenation) simplified the separation and purification for the produced metal hydride. Moreover, the study explores the potential for this method of NaH production to be used for NaBH4 production and regeneration for hydrogen export applications. This approach offers an alternative, cost-effective method for producing NaH.